ELECTRONIC SERVICE QUALITY AND E-PASSENGER SATISFACTION IN THE AVIATION INDUSTRY IN RIVERS STATE, NIGERIA (American Journal of Business Management, Economics and Banking, 2025)
The study investigated the effect of electronic service quality factors influencing e-passenger satisfaction to airlines in the tourism industry in Rivers State, Nigeria. The descriptive survey research gathered data from 138 airline passengers who patronised both domestic and foreign airlines in Nigeria. A well structured questionnaire containing 17 items, with four demographic items was used to elicit data from the respondents. The primary data generated from the questionnaire administration was utilised to validate the model developed for the study empirically through statistical tests with the help of Statistical Package for the Social Sciences (SPSS). The inferential statistical analysis showed that e-passenger satisfaction to the airlines was driven by accessibility, security, information quality, and service reliability. The study therefore concluded that acquiring robust e-business infrastructure is essential for tourism service providers like airlines that want to enhance e-passenger satisfaction. It was thus recommended that, to enhance or sustain the e-satisfaction of airline passengers towards e-transaction processes, the airline owners/managers should ensure that the websites are readily available 24/7 to enhance real time processing of the documentations required among others.